المشكلات الأسرية المعاصرة وحلها في ضوء مقاصد الشريعة = Contemporary family problems and their solutions in the light of purposes of Islamic law - Dengini, Kurorso; El-Seoudi, Abdel Wadoud Moustafa Moursi; Muhammad Husni, Ahmad (Universiti Kebangsaan Malaysia (UKM), 2014)
Nowadays, there are many family problems spreading in the society that lead to divorce and destabilized family. Therefore, the research tries to examine how to solve these problems from the perspectives of purposes of Islamic law and general rules of Islamic law. This research aims to highlight the reasons and motives that lead to the existence of these problems. The contemporary family issues are many, and so as not to expand these issues, the study will focus on two important problems, namely working wife, and domestic violence. The study uses inductive and analytical approach for collecting data. The views of Muslim scholars are gathered and then they are classified into agreement and disagreement based on a specific issue. The Muslim scholar’s views are displayed along with proof and evidence in the matter. The analysis of texts and issues is made in the light of the purposes of the law. The results are a wife is permissible to work according to Islam and it is not contrary to purposes of law, but subjected to regulations and restrictions, and the working women should balance his daily life between working outside and giving attention to family matters. Many issues arise in the Muslim family nowadays resulting from non-compliance with the rights, obligations and duties between the couples. Each couple should do commitment to the teachings of Islam and hold firmly its purposes of Islamic law as well as implement them in family life. Thus, it is hoped that the family life will always be in obedience to Allah.